Expanded polytetrafluoroethylene artificial blood vessel and manufacturing method thereof
By introducing a multi-layered structure of porous support layer, biodegradable layer and antithrombotic layer into expanded polytetrafluoroethylene artificial blood vessels, the problems of insufficient mechanical strength and compliance and antithrombotic properties of small-diameter artificial blood vessels are solved, and long-term patency and tissue regeneration are improved simultaneously.
Patent Information
- Application Number
- CN202511780886.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2026-03-17
AI Technical Summary
Existing small-diameter artificial blood vessels made of expanded polytetrafluoroethylene (ePTFE) have shortcomings in mechanical strength and compliance, antithrombotic properties, and synchronous tissue regeneration, leading to thrombosis and intimal hyperplasia, making it difficult to maintain patency in the long term.
The design employs a multi-layer structure, including a porous support layer, a biodegradable layer, and an antithrombotic layer. The mechanical properties and biocompatibility are improved by a silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide coating, and antithrombotic materials such as heparin, nitroglycerin, phosphorylcholine, elastin, and RGD peptide sequences are loaded to inhibit thrombus formation.
It improves the mechanical strength and biocompatibility of small-diameter artificial blood vessels, reduces the risk of thrombosis, promotes tissue regeneration and endothelialization, and ensures long-term patency and functional stability.
Smart Images

Figure CN121668385A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of biomedical materials, and particularly relates to an artificial blood vessel material for replacing or repairing small-caliber blood vessels and a preparation method thereof. BACKGROUND
[0002] Most of the currently marketed artificial blood vessels use synthetic polymer materials, such as polyester, polyurethane, expanded polytetrafluoroethylene, etc. Among them, expanded polytetrafluoroethylene (ePTFE) is a porous structure obtained by removing the lubricant and stretching the original fibrils after the polytetrafluoroethylene generated by emulsion polymerization is extruded into fibrils. This structure has excellent biological inertia, almost no inflammation and rejection reaction in the body, and good tissue compatibility; its mechanical properties are stable, can withstand arterial blood pressure for a long time, and the material is flexible and easy to suture. In addition, due to the porous structure, platelets can penetrate to form a false inner membrane, which is easy to pre-coagulate and can anastomose with the patient's blood vessels. However, for small-caliber artificial blood vessels, easy pre-coagulation means that thrombosis and intimal hyperplasia are easy to occur; high mechanical strength means that the compliance is insufficient, and the elastic modulus is not matched with the natural blood vessels, which is easy to cause turbulence after implantation; good durability means that the material degradation rate is difficult to synchronize with the tissue regeneration process, and the long-term patency rate is insufficient. Therefore, although expanded polytetrafluoroethylene is widely used in large-caliber blood vessels, there is still a great improvement space in small-caliber blood vessels.
[0003] In view of the above defects, in the aspect of surface modification, the prior art proposes coating an anticoagulant (such as heparin) on the surface of ePTFE to improve the patency rate (WO1995001190A1); adding tissue stimulating molecules (such as IGF-1, IGF-2, VEGF, etc.) to promote the migration of the patient's own endothelial cells, forming an in vivo inner membrane with anticoagulant function; or using drugs such as rapamycin and paclitaxel to inhibit the excessive proliferation of smooth muscle cells at the anastomosis site (WO2009064372A3). In addition, it is also proposed to regulate the pore size and distribution of the porous material to optimize the balance between tissue growth and endothelialization (WO1999047077A1), however, the synergistic optimization of ePTFE porosity and mechanical strength has limited effect in the small-caliber scenario. SUMMARY
[0004] In a first aspect, the present application provides a preparation method of an artificial blood vessel composed of a porous support layer, a biodegradable layer and an antithrombotic layer, the method comprising: 1) dissolving N-isopropyl acrylamide monomers and vinyl pyrrolidone monomers in a first solvent, adding an initiator after oxygen removal treatment, and performing a polymerization reaction at 60-80°C, and then separating and purifying the reaction product polyvinyl pyrrolidone-poly-N-isopropyl acrylamide; 2) dissolving silver nitrate and polyvinylpyrrolidone-poly-N-isopropylacrylamide prepared in step 1) in a second solvent to obtain a silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide solution; 3) immersing expanded polytetrafluoroethylene in the silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide solution prepared in step 2) so that the surface of the expanded polytetrafluoroethylene has a silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide coating, and then removing the second solvent to obtain a porous support layer; 4) dissolving a biodegradable material in a third solvent, coating the dissolved biodegradable material on the surface of the porous support layer prepared in step 3) by immersion, spraying or brushing, and then removing the third solvent to obtain a porous support layer with a biodegradable layer; and 5) loading an anti-thrombogenic material to the porous support layer with a biodegradable layer obtained in step 4) to obtain the artificial blood vessel; wherein the first solvent is water or a mixture of ethanol and water; the second solvent is selected from N,N-dimethylformamide, dimethyl sulfoxide or a mixture thereof; and the third solvent is selected from dichloromethane, trichloromethane, N,N-dimethylformamide or a mixture thereof; wherein the initiator is ammonium persulfate, azobisisobutyronitrile or a mixture thereof; wherein the biodegradable material is one or more selected from polylactic acid, polycaprolactone, poly(lactic-co-glycolic acid), polyglycolide and polyurethane; wherein the anti-thrombogenic material is one or more selected from heparin, nitroglycerin, phosphatidylcholine, tropoelastin, RGD peptide sequence, antithrombin III and tissue factor pathway inhibitor.
[0005] In preferred embodiments, in step 1), the ratio of N-isopropylacrylamide monomer to vinylpyrrolidone monomer is 1:9 to 9:1 (mol / mol). In some preferred embodiments, the first solvent is a mixture of water and ethanol, wherein the volume ratio of water to ethanol is 3:1 to 9:1. In other preferred embodiments, the first solvent is pure water. In preferred embodiments, the ratio of the first solvent to the total mass of monomers is 2:1 to 10:1; in some preferred embodiments, the initiator is a mixture of ammonium persulfate and azobisisobutyronitrile, wherein the mass ratio of ammonium persulfate to azobisisobutyronitrile is 1:9 to 9:1. In preferred embodiments, the total mass of the initiator is 0.1wt%-2wt% of the total mass of monomers.
[0006] In preferred embodiments, in step 2), the ratio of silver nitrate to polyvinylpyrrolidone-poly-N-isopropylacrylamide is 1:5-1:50 (wt / wt). In preferred embodiments, the silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide solution has a solid content of 10wt%-15wt%.
[0007] In preferred embodiments, in step 3), the expanded polytetrafluoroethylene has a porosity of 50%-90% and a mean pore size of 0.1-10μm.
[0008] In preferred embodiments, in step 4), the biodegradable material is a blend of polylactic acid and polycaprolactone, wherein the mass ratio of polylactic acid to polycaprolactone is 70:30 to 90:10; or the biodegradable material is a poly(lactic-co-glycolic acid) copolymer, wherein the mass ratio of lactic acid to glycolic acid is 50:50 to 85:15; or the biodegradable material is a blend of polylactic acid and polyglycolide, wherein the mass ratio of polylactic acid to polyglycolide is 20:80 to 50:50; or the biodegradable material is a polyurethane, wherein the mass ratio of soft segment to hard segment in the polyurethane is 70:30 to 30:70.
[0009] In preferred embodiments, in step 5), the anti-thrombosis material is one of heparin, nitroglycerin, phosphatidylcholine, tropoelastin, RGD peptide sequence, wherein the heparin is covalently immobilized on the surface of the porous support layer with biodegradable layer obtained in step 4) by plasma grafting technology, wherein the surface density of the heparin is 0.1-1 mg / cm2; wherein the nitroglycerin is immobilized on the surface of the porous support layer with biodegradable layer obtained in step 4) by chemical grafting or physical adsorption, wherein the content of the nitroglycerin on the surface is 0.5-2wt%; wherein the phosphatidylcholine is grafted to the surface of the porous support layer with biodegradable layer obtained in step 4) by ultraviolet grafting polymerization, wherein the grafting rate is 1-5%; wherein the tropoelastin is loaded on the surface of the porous support layer with biodegradable layer obtained in step 4) by electrospinning or immersion, wherein the content of the tropoelastin on the surface is 1-10wt%; wherein the RGD peptide sequence is immobilized on the surface of the porous support layer with biodegradable layer obtained in step 4) by chemical grafting or physical adsorption, wherein the surface density of the RGD peptide is 1-10nmol / cm2.
[0010] In some preferred embodiments, in step 5), the anti-thrombotic material is heparin, nitroglycerin, phosphatidylcholine, tropoelastin and RGD peptide, wherein the heparin is loaded onto the surface of the porous support layer with biodegradable layer obtained in step 4) by plasma grafting or impregnation, and then the nitroglycerin, phosphatidylcholine, tropoelastin and RGD peptide are sequentially immobilized by chemical grafting or physical adsorption, wherein the surface density of the heparin is 0.1-1 mg / cm2; the content of the nitroglycerin on the surface is 0.5-2 wt%; the grafting rate of the phosphatidylcholine is 1-5%; the content of the tropoelastin on the surface is 1-10 wt%; and the surface density of the RGD peptide is 1-10 nmol / cm2.
[0011] In some preferred embodiments, in step 5), the anti-thrombotic material is heparin, nitroglycerin, phosphatidylcholine, tropoelastin and RGD peptide, wherein the heparin is loaded onto the surface of the porous support layer with biodegradable layer obtained in step 4) by plasma grafting or impregnation, and then the nitroglycerin, phosphatidylcholine, tropoelastin and RGD peptide are sequentially immobilized by chemical grafting or physical adsorption, wherein the surface density of the heparin is 0.1-1 mg / cm2; the content of the nitroglycerin on the surface is 0.5-2 wt%; the grafting rate of the phosphatidylcholine is 1-5%; the content of the tropoelastin on the surface is 1-10 wt%; and the surface density of the RGD peptide is 1-10 nmol / cm2.
[0012] In the second aspect, the present application provides an artificial blood vessel prepared by the method of the first aspect. In preferred embodiments, the porous support layer of the artificial blood vessel has a thickness of 2-5 μm, and the biodegradable layer of the artificial blood vessel has a thickness of 8-20 μm. BRIEF DESCRIPTION OF DRAWINGS
[0013] Figure 1 Figure 1 is a schematic diagram of the three-layer structure of a human arterial blood vessel, wherein 1, 2 and 3 represent the adventitia, media and intima of the artificial blood vessel, respectively.
[0014] Figure 2 Figure 2 is a SEM image of the artificial blood vessel prepared in Example 1, wherein the upper panel shows the inside of the artificial blood vessel membrane, and the lower panel shows the outside of the artificial blood vessel membrane. DETAILED DESCRIPTION
[0015] The arterial blood vessel wall of a human body contains three layers, wherein the innermost intima is composed of endothelial cells, which directly contact with blood, and mainly functions to prevent coagulation and activation of complement factors, inhibit adhesion of leukocytes and platelets, and participate in the contraction and expansion, growth and remodeling of blood vessels. The outermost adventitia is composed of loose connective tissue, and mainly composed of fibroblasts at the cellular level, which is responsible for repairing when the blood vessel is damaged. The media between the intima and the adventitia is composed of smooth muscle cells, elastic tissue layer and a small amount of collagen, and mainly functions to resist repeated expansion and contraction caused by physiological pulsation of blood flow and intraluminal pressure, and provide mechanical strength and elasticity. Figure 1 .
[0016] In the present application, the artificial blood vessel is provided with an anti-thrombogenic layer, a biodegradable layer, and a porous support layer, which mimics the synergistic effect of the intima, media, and adventitia of a natural blood vessel.
[0017] The porous support layer functions similarly to the adventitia of a blood vessel and is obtained by soaking an expanded polytetrafluoroethylene substrate with silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide. Poly-N-isopropylacrylamide (PNIPAM) is a temperature-sensitive polymer material with a lower critical solution temperature (LCST) of about 32°C, close to the body temperature of humans. When the temperature is below the LCST, the hydrophilic groups (such as amide groups) on the PNIPAM molecular chain form hydrogen bonds with water molecules, allowing the material to have good hydrophilicity and swell in water. When the temperature is above the LCST, the hydrogen bonds are broken, and the hydrophobic isopropyl groups are exposed, causing the material to undergo a phase transition from a hydrophilic state to a hydrophobic state and shrink. Polyvinylpyrrolidone (PVP) is a water-soluble polymer with good biocompatibility and hydrophilicity. The polyvinylpyrrolidone-poly-N-isopropylacrylamide (PVP-PNIPAM) copolymer not only retains the temperature-sensitive properties of PNIPAM (i.e., achieving the swelling and shrinking properties of the gel upon temperature changes), but also improves the hydrophilicity and biocompatibility of the material.
[0018] Silver nitrate gradually releases silver ions in the material, which have broad-spectrum antibacterial ability and can inhibit the growth and reproduction of bacteria. Since bacterial infection is an important factor leading to vascular calcification, the antibacterial effect of silver ions can indirectly reduce the occurrence of calcification. Silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide can adjust its surface properties such as hydrophilicity and charge according to changes in the temperature environment. This dynamic adjustment ability can affect the deposition behavior of calcium and phosphorus ions in the blood on the material surface, further inhibiting calcification. In summary, by doping silver nitrate, the surface biocompatibility of the material can be significantly improved, reducing the non-specific adsorption of proteins and cells in the blood, thereby reducing the risk of calcification. In addition, since silver ions inhibit bacterial growth, they can also reduce the risk of infection.
[0019] In a preferred embodiment, the addition ratio of raw material N-isopropyl acrylamide monomer (NIPAM) to vinyl pyrrolidone monomer (NVP) is 1:9 to 9:1 (mol / mol). When the addition ratio of the two is less than 1:9 (i.e., the proportion of NIPAM is too low), the structural units with temperature-sensitive properties in the copolymer decrease, resulting in a significant weakening of the temperature-sensitive properties of the copolymer. When the temperature changes, the surface properties of the material (such as hydrophilicity, charge, etc.) are difficult to undergo significant dynamic adjustment, thereby affecting its ability to regulate the deposition behavior of calcium and phosphorus ions in blood, which is not conducive to inhibiting vascular calcification. At the same time, the reduction effect of non-specific adsorption of proteins and cells in blood will also be reduced, thereby failing to effectively reduce the risk of calcification and reduce the risk of infection. Due to the inability to fully exhibit sufficient hydrophilicity and biocompatibility effects, it may cause the components in the blood to be more easily adsorbed on the surface of the material when the material is in contact with the blood, increasing the potential risk of thrombosis and affecting the blood compatibility of the artificial blood vessel. When the addition ratio is higher than 9:1 (i.e., the proportion of NIPAM is too high), the mechanical properties and elasticity may be poor. Specifically, NVP helps to improve the overall performance of the material, and when the proportion of NIPAM is too high, the relative content of NVP in the copolymer is too low, which may affect the mechanical properties and elasticity of the copolymer. For artificial blood vessels, stable mechanical properties are crucial and need to be able to withstand arterial blood pressure for a long time. If the mechanical properties of the copolymer are poor, it may not be able to withstand the pressure during the circulation of human blood, leading to abnormal morphology and function of the blood vessel and affecting the service life and patency rate of the artificial blood vessel. Although NIPAM has good biocompatibility, a too high proportion of NIPAM may disrupt the balance of the biocompatibility of the copolymer. The human body environment is complex, and appropriate biocompatibility requires the synergy of multiple factors. A too high proportion of NIPAM may change the interaction between the copolymer and the surrounding tissue, triggering unnecessary immune or inflammatory reactions, which is not conducive to the long-term stable existence and function of the material in the body. N-isopropyl acrylamide monomer (NIPAM) and vinyl pyrrolidone monomer (NVP) are preferably of analytical purity. Before use, NIPAM can be refined, for example, impurities can be removed by recrystallization to improve the efficiency of the polymerization reaction and the quality of the product. Due to the strong water solubility and reactivity of NVP, attention should be paid to avoid contact with oxygen, moisture, etc. in the air during storage and use to prevent self-polymerization or other side reactions.
[0020] Since NIPAM and NVP have certain hydrophilicity, the first solvent is a hydrophilic solvent, which can be water or a mixture of water and ethanol. The preferred mixing ratio of water and ethanol is usually water: ethanol = 3: 1 to 9: 1 (volume ratio). Alternatively, the first solvent is water, which can well dissolve the two monomers and is an environmentally friendly green solvent. In a preferred embodiment, the ratio of the total mass of the solvent and the monomer is 2: 1 to 10: 1, so that the reactants have the highest possible concentration while ensuring the solubility of the monomers.
[0021] After dissolving N-isopropyl acrylamide and vinyl pyrrolidone in the first solvent, nitrogen is introduced to remove oxygen to prevent oxygen from inhibiting the free radical polymerization reaction. In a preferred embodiment, the deoxygenation treatment time is 30-60 minutes. After deoxygenation treatment, the initiator is added, the reaction kettle is sealed, and the reaction is carried out at 60-80°C. Under the action of the initiator, the double bonds in the monomer molecules of NIPAM and NVP are opened to form free radicals. These free radicals combine with each other to start the chain growth reaction and gradually form polymer chains. Since NIPAM and NVP exist in the reaction system at the same time, they will participate in the polymerization reaction together to ultimately generate PVP-PNIPAM copolymer. The initiator capable of initiating the polymerization of the monomers is, for example, ammonium persulfate (APS) and azobisisobutyronitrile (AIBN). The initiator can be single or mixed, and the mass ratio of ammonium persulfate to azobisisobutyronitrile can be set to 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, etc. In a preferred embodiment, the amount of initiator is 0.1wt%-2wt% of the total mass of the monomers. In a preferred embodiment, the reaction time is 6-12 hours. When the amount of initiator is less than 0.1wt%, the number of free radicals generated is extremely small, and the polymerization reaction is almost difficult to effectively proceed, the reaction time will be significantly prolonged, and even the desired polymerization degree may not be reached, resulting in extremely low monomer conversion and insufficient polymer yield. When the amount of initiator is higher than 2wt%, excessive initiator will generate a large number of free radicals, which will initiate too many polymerization chains, resulting in too few monomers combined per polymerization chain, and thus the molecular weight of the polymer is too low. Low molecular weight polymers may not meet the mechanical performance requirements of artificial blood vessels and other application scenarios, such as insufficient strength and elasticity, affecting the performance and service life of artificial blood vessels. Excessive amount of initiator may cause the temperature of the reaction system to rise sharply, which may trigger a series of side reactions such as self-polymerization and oxidation of monomers. These side reactions will generate impurities, reduce the purity and quality of the polymer, and may also affect the biocompatibility and other properties of the polymer.
[0022] After the polymerization reaction is completed, the reaction mixture is cooled to room temperature. In embodiments where water is used as the solvent, the copolymer can be precipitated by adding an appropriate amount of an organic solvent (e.g., ethanol, acetone, etc.), and then the precipitate can be separated by filtration. The separated precipitate can be washed with water or ethanol to remove unreacted monomers, initiators, and other impurities, and then dried. By performing this step 1), a purified polyvinylpyrrolidone-poly-N-isopropylacrylamide (PVP-PNIPAM) copolymer is obtained. The PVP-PNIPAM copolymer has good swelling properties due to the strong hydrophilicity of PVP, which can form hydrogen bonds with water molecules through groups such as carbonyl and ether oxygen groups on its molecular chain, thereby absorbing a large amount of water to cause the copolymer to swell. At the same time, PNIPAM has unique temperature sensitivity. When the temperature is lower than its lower critical solution temperature (LCST, about 32°C), the hydrophilic groups (such as amide groups) on the PNIPAM molecular chain form hydrogen bonds with water molecules, making the material have good hydrophilicity and swell in water. When the temperature is higher than the LCST, the hydrophilicity of the PNIPAM segment changes, the hydrogen bonds are broken, and the hydrophobic isopropyl group is exposed, causing the material to undergo a phase transition from a hydrophilic state to a hydrophobic state and shrink, and the swelling properties change accordingly. This temperature sensitivity allows the copolymer to adjust its surface properties, such as hydrophilicity and charge, according to changes in the environmental temperature. In the physiological environment of the body (near 37°C), the appropriate swelling properties allow the copolymer to absorb a certain amount of water, maintain a certain degree of flexibility and elasticity, and simulate the physiological state of natural blood vessels. At the same time, the swelling properties also help to provide a suitable water environment for cell adhesion, proliferation, and differentiation, promoting tissue repair and endothelialization. PNIPAM is the key component that gives the copolymer temperature sensitivity. The PVP-PNIPAM copolymer has a certain mechanical strength and flexibility. PVP provides a certain degree of hydrophilicity and flexibility, while PNIPAM can also increase the structural stability of the material to some extent.
[0023] In the embodiments using water or water and ethanol mixed solvents, ethanol or acetone can still be used to precipitate the copolymer. This is because ethanol and acetone are common organic solvents that can reduce the solubility of the copolymer in the solvent, thereby causing the copolymer to precipitate from the mixed solution. Ethanol is a relatively mild organic solvent, relatively friendly to the environment and operating personnel. When an appropriate amount of ethanol is added to the water and ethanol mixed solvent, the solubility of the copolymer in the mixed solvent decreases, and a precipitate gradually forms. The precipitate can be separated by filtration, and then the separated precipitate can be washed with water or ethanol to remove unreacted monomers, initiators and other impurities. Acetone has stronger solubility and the precipitation effect can be more obvious. However, acetone has volatility and certain toxicity, and should be used in a well-ventilated environment and with safety precautions. Similarly, the copolymer will precipitate after the addition of acetone, and the purified copolymer can be obtained through steps such as filtration, washing and drying.
[0024] In step 2), silver nitrate is mixed with the polyvinylpyrrolidone-poly-N- isopropylacrylamide prepared in step 1) in a second solvent to obtain silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide. In a preferred embodiment, the mixing ratio of silver nitrate to PVP-PNIPAM is 1:5 to 1:50 (wt / wt). When the ratio is lower than 1:50 (i.e., the proportion of silver nitrate is too low), the antibacterial performance is insufficient. Silver nitrate has broad-spectrum antibacterial ability, and its antibacterial effect is mainly achieved by releasing silver ions. Silver ions can bind to sulfhydryl groups on the bacterial cell membrane, destroy the structure and function of the bacterial cell membrane, and cause bacterial content to leak, thereby inhibiting the growth and reproduction of bacteria. Specifically, when the content of silver nitrate is relatively low, the amount of silver ions released is insufficient to effectively inhibit the growth of bacteria, especially in some environments susceptible to bacterial contamination, such as the inside of human blood vessels, the risk of bacterial infection increases. Bacterial infection and abnormal deposition of calcium and phosphorus ions in blood are important causes of vascular calcification. In addition to the antibacterial effect, the silver ions released by silver nitrate can also affect the deposition behavior of calcium and phosphorus ions in the blood on the material surface, reducing the formation of calcified substances. When the content of silver nitrate is too low, its regulation effect on the deposition of calcium and phosphorus ions is weakened, and it cannot effectively inhibit the occurrence of vascular calcification. Vascular calcification can cause the elasticity of artificial blood vessels to decrease, the lumen to narrow, and affect the normal flow of blood, reducing the patency rate of artificial blood vessels. When the ratio is higher than 1:5 (i.e., the proportion of silver nitrate is too high), the biocompatibility of the material decreases. Although silver nitrate has advantages such as antibacterial effect, excessive silver nitrate can be toxic to human tissues. When the mixing ratio of silver nitrate to PVP-PNIPAM is higher than 1:5, a large amount of silver ions may be released in the body, which can cause adverse reactions with human cells, damage the structure and function of cells, cause inflammatory reactions and tissue damage, and reduce the biocompatibility of the material. Excessive silver nitrate can affect the molecular structure and physical and chemical properties of PVP-PNIPAM. For example, silver nitrate can interact with certain groups on the PVP-PNIPAM molecular chain, change the arrangement and conformation of the molecules, and thus affect the swelling, hydrophilicity, temperature sensitivity, and other properties of the copolymer.
[0025] The second solvent for dissolving silver nitrate and PVP-PNIPAM can be N,N- dimethylformamide (DMF), dimethyl sulfoxide (DMSO) or a mixture thereof. Both solvents have good solubility for PVP-PNIPAM and can also dissolve silver nitrate to some extent, so that silver nitrate is uniformly dispersed in the PVP-PNIPAM solution. Among them, DMF is better in solubility and volatility, while DMSO has high polarity and good solubility for various organic and inorganic substances. In a preferred embodiment, the volume ratio of DMF to DMSO can be 1:3-3:1. In a preferred embodiment, the ratio of the total mass of silver nitrate and PVP-PNIPAM to the mass of the second solvent is 1:5 to 1:10. At this concentration range, the solvent has sufficient amount to fully dissolve PVP-PNIPAM and dissolve and disperse silver nitrate. PVP-PNIPAM and silver nitrate can be uniformly dispersed in the solvent to form a uniform solution. This is because there is good interaction between the solvent and the solute, which can break the intermolecular forces of the solute molecules, so that the solute molecules are uniformly distributed in the solvent. The appropriate concentration can make the solution have appropriate viscosity. When the ratio of the total mass of silver nitrate and PVP-PNIPAM to the mass of the second solvent is 1:5 to 1:10, the solution has moderate viscosity, which will not be too thin to cause the solution to flow too fast during coating, making it difficult to form a uniform coating on the surface of the substrate (such as expanded polytetrafluoroethylene), nor will it be too viscous to cause coating difficulty and fail to uniformly cover the surface of the substrate.
[0026] In step 3), the expanded polytetrafluoroethylene is immersed in the silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropyl acrylamide prepared in step 2) so that the surface of the expanded polytetrafluoroethylene has a coating of silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropyl acrylamide, and then the second solvent is removed to obtain a porous support layer. The expanded polytetrafluoroethylene (ePTFE) as the substrate is prepared according to conventional methods in the art. The porosity of the expanded polytetrafluoroethylene is preferably 50%-90%, the average micropore size is preferably 0.1-10 μm, and the wall thickness is preferably 0.4-0.6 mm. The inventors found that increasing the porosity can promote tissue ingrowth and enhance endothelialization of cells along the surface, thereby improving healing rate, however, due to the tubular structure of the artificial blood vessel, higher porosity also means lower mechanical structure. By optimizing the porosity, tensile strength and micropore size of the expanded polytetrafluoroethylene, the substrate is more suitable for small-diameter artificial blood vessels (diameter ≤6 mm).
[0027] In a preferred embodiment, the expanded polytetrafluoroethylene (ePTFE) is completely immersed in the silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide solution for 1-8 hours or even longer to ensure that the composite solution fully penetrates into each part of the porous layer. The immersion can generally be carried out at room temperature (20-25°C), however, the immersion temperature can also be appropriately increased to 30-40°C to accelerate the dissolution and penetration speed, and the temperature should not exceed the tolerance temperature of the solvent and the material. After the coating reaction is completed, the material is placed in a vacuum drying oven and dried at 30-40°C under a vacuum degree of 100-1000 Pa of absolute pressure for 2-4 h, and through this operation, the solvent can be quickly removed to avoid damage to the material at high temperature. By implementing step 3), the PVP-PNIPAM containing silver nitrate is loaded into the expanded polytetrafluoroethylene to obtain a porous support layer. The porous support layer has a function similar to the adventitia of blood vessels, providing structural support while allowing the porous structure to promote cell adhesion, proliferation, and differentiation. As described above, due to the porosity of 50-90%, suitable space is provided for cell adhesion and growth, which helps tissue repair and reconstruction. The thickness of the porous support layer is preferably 2-5 μm. By applying the porous support layer, the artificial blood vessel has a tensile strength of 1-10 MPa and a radial burst strength of ≥500 mmHg, so it can withstand the pressure during the circulation of human blood, maintain the normal morphology and function of the blood vessel, and improve the accessibility of the artificial blood vessel. N-isopropylacrylamide monomer, vinylpyrrolidone monomer, silver nitrate, and expanded polytetrafluoroethylene are inexpensive, and all materials are non-toxic to the human body, with extremely high safety.
[0028] Subsequently, by implementing step 4), the biodegradable material is assembled to the porous support layer. Specifically, the biodegradable material is dissolved in a third solvent, and the dissolved biodegradable material is coated on the surface of the porous support layer prepared in step 3) by immersion, spraying or brushing, and then the third solvent is removed to obtain a porous support layer with a biodegradable layer. After the biodegradable material is assembled to the porous support layer, it can provide a relatively stable and strong structural foundation for the subsequent antithrombotic layer. The porous support layer is similar to the adventitia of blood vessels, and after the biodegradable material is assembled, it is equivalent to simulating the media of blood vessels, further providing mechanical support and playing a key role in promoting tissue regeneration.
[0029] The biodegradable material can be one or more of polylactic acid (PLA), polycaprolactone (PCL), poly(lactic-co-glycolic acid) (PLGA), polyglycolide (PGA), and polyurethane (PU). In some embodiments, the biodegradable material is a blend of polylactic acid and polycaprolactone, with a mass ratio of polylactic acid to polycaprolactone of 70:30 to 90:10. When the mass ratio of the two is less than 70:30, the degradation rate is too fast and the mechanical properties are too weak; when the mass ratio of the two is greater than 90:10, the degradation rate is too slow and the mechanical properties are too strong, and the elasticity is not enough. Within this range, the ratio can be adjusted according to the site of use, for example, for sites that require faster degradation, 70:30 to 80:20 can be used; for sites that require long-term support, 85:15-90:10 can be used.
[0030] In some embodiments, the biodegradable material can be poly(lactic-co-glycolic acid). The ratio of lactic acid and glycolic acid in the poly(lactic-co-glycolic acid) can be adjusted to obtain a suitable degradation rate and mechanical properties. In preferred embodiments, the ratio of lactic acid and glycolic acid in the copolymer is 50:50 to 85:15. For sites that require faster degradation, 50:50 to 75:25 can be used; for sites that require long-term support, 75:25-85:15 can be used.
[0031] In some embodiments, the biodegradable material is polyglycolide. Polyglycolide is suitable for sites that require rapid degradation. In addition, a blend of polylactic acid and polyglycolide can also be used. In such embodiments, the PGA:PLA is preferably 20:80 to 50:50 (mass ratio) to balance the degradation rate and mechanical properties.
[0032] In other embodiments, the biodegradable material can be polyurethane, and in preferred embodiments, the ratio of soft segment to hard segment of the polyurethane is 70:30 to 30:70 (mass ratio). The higher the proportion of hard segment, the higher the mechanical strength of the material, but the degradation rate is relatively slow; the higher the proportion of soft segment, the better the flexibility and the faster the degradation.
[0033] The selected biodegradable material is dissolved in a suitable solvent (such as dichloromethane, trichloromethane, N,N-dimethylformamide (DMF), etc.) to form a uniform solution. The porous support layer prepared in step 3) (i.e., ePTFE coated with silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide) is immersed in the biodegradable material solution, or the solution is uniformly coated on the surface of the porous support layer by spraying, brushing, or the like. The coated material is placed in a fume hood or a vacuum drying oven to remove the solvent, so that the biodegradable material forms a thin film or coating on the surface of the porous support layer. The thickness of this layer is 8-20 μm, equivalent to the middle membrane, which plays a key role in providing mechanical support and promoting tissue regeneration in the membrane of a small-diameter artificial blood vessel. Selecting the appropriate material and its ratio is crucial to ensuring the long-term patency and functionality of the artificial blood vessel.
[0034] Subsequently, by implementing step 5), the anti-thrombotic material is loaded into the porous support layer with a biodegradable layer obtained in step 4), obtaining the artificial blood vessel. In the artificial blood vessel, the biodegradable material can gradually release some bioactive substances during the degradation process, promoting tissue regeneration and vascular remodeling. On this basis, loading the anti-thrombotic layer can better interact with the newly formed tissue and exert an anti-thrombotic effect. Assembling the biodegradable material first allows it to fully play a role in promoting tissue growth, creating a more favorable microenvironment for the anti-thrombotic layer. Conversely, if the anti-thrombotic layer is loaded first, the subsequent assembly of the biodegradable material may damage the anti-thrombotic layer, affecting its anti-thrombotic properties.
[0035] The anti-thrombotic layer is a key part of preventing thrombus formation, and the material used in the anti-thrombotic layer has anticoagulant properties, such as one or more of heparin, nitroglycerin ester, phosphorylcholine, Tropoelastin, and RGD peptide sequences. In addition, the anti-thrombotic material can further include bioactive molecules such as antithrombin III (AT-III), tissue factor pathway inhibitor (TFPI), etc., to further enhance the anti-thrombotic effect. In the present invention, the above-mentioned materials are also referred to as anti-thrombotic materials, and their functionality can be ensured by treatment.
[0036] Heparin is a natural anticoagulant that can effectively inhibit platelet aggregation and thrombin formation. Heparin can be covalently immobilized on the surface of the biodegradable layer by plasma grafting technology, or it can be loaded onto the surface of the membrane by immersion, spraying, or the like. The density of heparin on the surface of the membrane is preferably 0.1-1 mg / cm².
[0037] Nitroglycerin ester can release nitric oxide (NO), which has strong anti-platelet aggregation and vasodilation effects. Nitroglycerin ester is fixed on the surface of the membrane by chemical grafting or physical adsorption to ensure its slow release of NO. The content of nitroglycerin ester on the surface of the membrane is preferably 0.5-2 wt%.
[0038] Phosphorylcholine (MPC) is a biomimetic material that can simulate the phospholipid bilayer structure on the surface of the cell membrane, reducing platelet adhesion and activation. MPC can be grafted onto the surface of the membrane by UV grafting polymerization to form an antithrombotic coating. The grafting rate is preferably 1-5%.
[0039] Tropoelastin can simulate the function of natural elastin, improve the elasticity and compliance of blood vessels, and also has certain antithrombotic effect. Tropoelastin can be loaded onto the surface of the membrane by electrospinning or immersion. The content of tropoelastin on the surface of the membrane is preferably 1-10 wt%.
[0040] RGD peptide sequence can enhance specific binding with cell integrin, promote endothelial cell adhesion and proliferation, thereby accelerating the endothelialization process and reducing thrombus formation. RGD peptide sequence is fixed on the surface of the membrane by chemical grafting or physical adsorption. The density is preferably 1-10 nmol / cm².
[0041] Different materials have different antithrombotic mechanisms, and mixed use can achieve functional complementation and inhibit thrombus formation from multiple aspects. For example, the anticoagulant effect of heparin, the anti-platelet aggregation effect of nitroglycerin ester, the effect of phosphorylcholine (MPC) on reducing platelet adhesion, and the promotion effect of tropoelastin and RGD peptide sequence on vascular endothelialization synergize with each other, which can more comprehensively prevent thrombus formation. The mixing method can use a step-by-step loading method, first loading heparin onto the surface of the membrane by plasma grafting or immersion, and then sequentially fixing nitroglycerin ester, phosphorylcholine (MPC), tropoelastin and RGD peptide sequence by chemical grafting or physical adsorption. This method takes into account the compatibility between materials and the effect of loading sequence on the final performance. Some materials can be mixed first and then loaded.
[0042] The antithrombotic layer is similar to the intima of the human arterial blood vessel, and its main function is to prevent thrombus formation and promote smooth blood flow.
[0043] The artificial blood vessel prepared by the method has an antithrombotic layer, a biodegradable layer, and a porous support layer. The matching with the temperature-sensitive polymer material is realized while the plunger is extruded by coating the silver nitrate-deposited copolymer on the surface of the ePTFE hollow fiber membrane; then, the biodegradable layer is further applied to the membrane surface; and the antithrombotic material such as heparin and NO-releasing molecules is loaded to the surface of the artificial blood vessel by a surface modification technique (such as a plasma grafting technique and an atomic layer deposition technique). According to the embodiment of the application, the amount of platelet adhesion is reduced to <7 cells / mm2 in vitro by the synergistic effect of the three layers; the radial burst strength of the artificial blood vessel is ≥500 mmHg, the compliance is similar to that of the carotid artery (elastic modulus 1-3 MPa), and the mechanical properties match those of the natural blood vessel. It can be seen that the artificial blood vessel prepared by the method can realize the optimization of blood compatibility, effectively inhibit the non-specific adsorption of proteins, and achieve good shear stress response characteristics, solving the problems of easy thrombosis, poor compliance, and low endothelialization efficiency of the current artificial blood vessel. EMBODIMENT
[0044] EMBODIMENT 1 A reaction kettle with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet device was used for the reaction. The stirrer was used to mix the reactants sufficiently to ensure the uniformity of the reaction; the thermometer was used to monitor the temperature of the reaction system in real time; the reflux condenser could prevent the loss of the solvent during the reaction; and the nitrogen inlet device was used to introduce nitrogen into the reaction system to remove oxygen in the system and prevent the inhibition of the free radical polymerization reaction by oxygen.
[0045] The raw materials N-isopropyl acrylamide monomer (NIPAM) and vinyl pyrrolidone monomer (NVP) were both of analytical purity, and before use, the impurities in NIPAM were removed by recrystallization.
[0046] 1) 8.00 g of N-isopropyl acrylamide and 2.00 g of vinyl pyrrolidone (mass ratio 8:2, molar ratio 7.3:2.7) were dissolved in 100 mL of pure water, oxygen was removed by nitrogen for 60 minutes, then 0.15 g of ammonium persulfate was added, and the reaction was carried out at 60°C for 12 hours. After the polymerization reaction was completed, the reaction was cooled to room temperature, 500 mL of ethanol was added to precipitate the copolymer, and after filtration and purification, the copolymer was washed with ethanol again to remove unreacted monomers, initiators and other impurities. After vacuum drying at 60°C for 12 hours, 9.42 g of purified polyvinyl pyrrolidone-poly-N-isopropyl acrylamide copolymer (PVP-PNIPAM) was obtained, with a yield of 94.2%.
[0047] 2) 0.50 g of silver nitrate was mixed with 5.00 g of the above PVP-PNIPAM copolymer (mass ratio 1:10), which was dissolved in 45 mL of DMF-DMSO mixed solvent (DMF:DMSO volume ratio = 2:1) to obtain a silver nitrate doped polyvinylpyrrolidone-poly-N-isopropylacrylamide solution (PVP-PNIPAM-Ag) with a solid content of 10.9 wt%.
[0048] 3) At room temperature (25°C), the expanded polytetrafluoroethylene tube blank (outer diameter 4 mm, wall thickness 0.5 mm, porosity 70%, average pore size of micropores 2 μm, polytetrafluoroethylene dispersion resin (Daikin F106), mixed with Exxon Mobil Isopar L lubricant at a mass ratio of 100:25, mixed uniformly and sealed tightly. At 40°C, it was placed in an electric heating constant temperature drying oven for 24 h. The paste was slowly poured into the extruder cavity, and the type blank was extruded by controlling the pressure. After 10 min of pressure retention, the type blank was forced to extrude from the die by the pushing action of the plunger to obtain the preform. Then, stretching was performed at a process parameter of 180°C, and sintering was performed at 360°C. 0.80 g of the PVP-PNIPAM-Ag solution prepared in step 2) was weighed and soaked for 8 hours, during which a vacuum-atmospheric pressure cycle was applied every 30 min (-0.09 MPa / 5 min→atmospheric pressure / 5 min) to ensure that the composite solution fully penetrated into each part of the expanded polytetrafluoroethylene porous layer. Subsequently, the reactants were placed in a vacuum drying oven, and vacuum drying was performed at 30°C for 2 h to obtain a porous support layer; the weight gain was 0.10 g, and the coating thickness (SEM section) was 3.2 μm.
[0049] 4) Biodegradable material polylactic acid-glycolic acid copolymer PLGA (LA:GA=75:25, η=0.65 dL / g, 1.50 g) was dissolved in 10 mL of dichloromethane to prepare a 15 wt% solution. The porous support layer prepared in step 3) was vertically immersed, and the solvent was evaporated at room temperature at a uniform speed of 5 mm / s. The process was repeated twice to obtain a porous biodegradable layer with a thickness of 12 μm and a fiber diameter of 0.8-1.2 μm; the overall weight gain was 0.07 g.
[0050] 5) The antithrombotic material was loaded into the porous support layer with a biodegradable layer obtained in step 4): ① Heparinization: 0.5 wt% heparin sodium aqueous solution was activated with 0.1 M EDC / 0.05 M NHS for 15 min, and the porous support layer with a biodegradable layer was immersed, shaken at 37°C for 2 h, washed with deionized water, and dried with nitrogen. The heparin density was 0.42 mg / cm²; ② Grafting of phosphorylcholine (MPC): 0.5 wt% MPC + 0.1 wt% benzophenone ethanol solution was used for surface grafting under 365 nm UV, the energy density was 3 J / cm², and the grafting rate was 3.1%.
[0051] The artificial blood vessel was finally obtained, with a total wall thickness of 0.53 mm. The performance test results of the artificial blood vessel prepared are as follows: 1) Radial burst strength: 580 mmHg (measured according to ISO 7198 method).
[0052] 2) Compliance: 2.1 % / 100 mmHg (tested according to the compliance test standard in ISO 7198:2016 "Cardiovascular implants - Vascular prostheses", which is similar to the compliance of the dog carotid artery.
[0053] 3) In vitro platelet adhesion: 4 cells / mm² (measured according to the ISO 10993-4 method, SEM counting, 2h perfusion, shear rate 1000 s⁻¹).
[0054] 4) Zone of inhibition test: Zone of inhibition against S. aureus was 22 mm (determined by disc diffusion method, measured the diameter of the sterile area after 24h culture. The test method is ISO 20776-1:2019 Test method for antimicrobial susceptibility testing).
[0055] 5) Cell viability (MTT): 98 % (measured according to the ISO 10993-5 method, the tested cells were L929 cells, cultured for 48h).
[0056] 6) 30-day New Zealand white rabbit carotid artery replacement: the number of test animals n=6, patency rate 95 %, intima intact, no stenosis, local calcification score 0.3 (Von Kossa staining) (tested according to ISO 10993-6:2017 Biological evaluation of medical devices. Part 6: Local effects test after implantation, verified by dissection, ultrasound and histology).
[0057] Example 2 Analogous method to Example 1 was used, wherein, 1) 9.00g N-isopropyl acrylamide and 1.00g vinylpyrrolidone (mass ratio 9:1, molar ratio 8.8:1.2) were dissolved in 100 mL pure water, deoxygenated by nitrogen for 60 minutes, then 0.15g ammonium persulfate was added, and reacted at 60°C for 12 hours. After the polymerization reaction was completed, the reaction was cooled to room temperature, precipitated with ethanol, washed and dried to obtain 9.38g of purified polyvinylpyrrolidone-poly-N-isopropyl acrylamide copolymer (PVP-PNIPAM), with a yield of 93.8%.
[0058] 2) 0.50 g of silver nitrate was mixed with 5.00 g of the above-mentioned PVP-PNIPAM copolymer (mass ratio 1:10), which was dissolved in 45 mL of a DMF-DMSO mixed solvent (DMF:DMSO volume ratio = 2:1) to obtain a silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide solution (PVP-PNIPAM-Ag) with a solid content of 10.9 wt%.
[0059] 3) At room temperature (25°C), the expanded polytetrafluoroethylene tube blank (outer diameter 4 mm, wall thickness 0.5 mm, porosity 70%, average pore size of micropores 2 μm, weight 0.80 g) was immersed in the PVP-PNIPAM-Ag solution prepared in step 2) for 8 hours, during which a vacuum-atmospheric pressure cycle was applied every 30 min (-0.09 MPa / 5 min→atmospheric pressure / 5 min) to ensure that the composite solution was fully infiltrated into each part of the expanded polytetrafluoroethylene porous layer. Subsequently, the reactants were placed in a vacuum drying oven and vacuum dried at 30°C for 2 h to obtain a porous support layer; the weight gain was 0.10 g, and the coating thickness (SEM section) was 3.1 μm.
[0060] 4) The biodegradable material polylactic acid-glycolic acid copolymer PLGA (LA:GA = 75:25, η = 0.65 dL / g, 1.50 g) was dissolved in 10 mL of dichloromethane to prepare a 15 wt% solution. The porous support layer prepared in step 3) was vertically immersed, pulled at a uniform speed of 5 mm / s, and the solvent was volatilized at room temperature, and the process was repeated twice to obtain a porous biodegradable layer with a thickness of 12 μm and a fiber diameter of 0.8-1.2 μm; the overall weight gain was 0.07 g.
[0061] 5) The antithrombotic material was loaded to the porous support layer with a biodegradable layer obtained in step 4): ① Heparinization: 0.5 wt% heparin sodium aqueous solution was activated with 0.1 M EDC / 0.05 M NHS for 15 min, and the porous support layer with a biodegradable layer was immersed, shaken at 37°C for 2 h, washed with deionized water, and dried with nitrogen; the heparin density was 0.40 mg / cm²; ② Grafting of phosphorylcholine (MPC): surface grafting was performed with 0.5 wt% MPC + 0.1 wt% benzophenone ethanol solution under 365 nm UV, the energy density was 3 J / cm², and the grafting rate was 3.0%.
[0062] The performance test results of the artificial blood vessel prepared are as follows (the determination method is the same as that of Example 1): Example 3 The similar method as in Example 1 was used, wherein in Step 1), 1.00 g of N-isopropylacrylamide and 9.00 g of vinylpyrrolidone (mass ratio 1:9, molar ratio 0.9:9.1) were dissolved in 100 mL of pure water, and deoxygenation was performed by passing nitrogen for 60 minutes, followed by the addition of 0.15 g of ammonium persulfate, and reaction at 60°C for 12 hours. After the completion of the polymerization reaction, the reaction was cooled to room temperature, and ethanol was precipitated, washed, and dried to obtain 9.4 g of purified polyvinylpyrrolidone-poly-N-isopropylacrylamide copolymer (PVP-PNIPAM) at a yield of 94%.
[0063] Steps 2) to 5) were the same as in Example 1.
[0064] The performance test results of the artificial blood vessels prepared are as follows (the determination method was the same as in Example 1): Example 4 The similar method as in Example 1 was used, wherein in Step 2), 0.10 g of silver nitrate and 5.00 g of PVP-PNIPAM copolymer (mass ratio 1:50) were mixed, and dissolved in 45 mL of DMF-DMSO mixed solvent (DMF:DMSO volume ratio = 2:1) to obtain a silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide solution (PVP-PNIPAM-Ag) with a solid content of 10.2 wt%.
[0065] The other steps were the same as in Example 1.
[0066] The performance test results of the artificial blood vessels prepared are as follows (the determination method was the same as in Example 1): Example 5 The similar method as in Example 1 was used, wherein in Step 2), 1.00 g of silver nitrate and 5.00 g of PVP-PNIPAM copolymer (mass ratio 1:5) were mixed, and dissolved in 45 mL of DMF-DMSO mixed solvent (DMF:DMSO volume ratio = 2:1) to obtain a silver nitrate-doped polyvinylpyrrolidone-poly-N-isopropylacrylamide solution (PVP-PNIPAM-Ag) with a solid content of 11.8 wt%.
[0067] The other steps were the same as in Example 1.
[0068] The performance test results of the artificial blood vessels prepared are as follows (the determination method was the same as in Example 1): Example 6 The similar method of Example 1 was adopted, wherein, in step 5), after heparin was loaded onto the surface of the porous support layer with biodegradable layer obtained in step 4) by the method of plasma grafting or immersion, nitroglycerin, phosphocholine, proelastin and RGD peptide were sequentially immobilized by the method of chemical grafting or physical adsorption. Specifically: ① Heparinization: 0.5wt% heparin sodium aqueous solution was activated with 0.1M EDC / 0.05M NHS for 15min, and the porous support layer with degradation layer was immersed, shaken at 37℃ for 2h, washed with deionized water, and dried with nitrogen. The heparin density was 0.45mg / cm²; ② Nitroglycerin immobilization: 5wt% nitroglycerin ethanol solution was prepared, and the tube blank treated in ① was immersed in the solution, and physically adsorbed at room temperature for 4h. The solvent was removed by vacuum drying (30℃, 2h), and the surface nitroglycerin content was 1.2wt%; ③ Grafting of phosphocholine (MPC): 0.5wt% MPC + 0.1wt% benzophenone ethanol solution was prepared, and ultraviolet light was irradiated for grafting (energy density 3J / cm², irradiation time 30min). After washing, vacuum drying was performed, and the MPC grafting rate was 3.3%; ④ Proelastin loading: 2wt% proelastin PBS solution (pH=7.4) was prepared, and the tube blank treated in ③ was immersed in the solution, and immersed at 4℃ overnight. After taking out, it was washed with PBS for 2 times, and freeze-dried (-40℃, 8h). The surface proelastin content was 5.8wt%; ⑤ RGD peptide sequence immobilization: 0.1mM RGD peptide PBS solution was prepared, and 0.05M EDC was added and activated for 10min. The tube blank was immersed, and chemically grafted at room temperature for 3h. After washing with deionized water to remove unbound peptides, it was dried with nitrogen. The surface density of RGD peptide was 4.2nmol / cm².
[0069] The final product parameters were as follows: total wall thickness 0.54mm, radial burst strength 510mmHg, and compliance 2.3% / 100mmHg.
[0070] The performance test results of the artificial blood vessel prepared are as follows (the determination method is the same as that of Example 1): By the multi-component synergistic loading of heparin (anticoagulation) + nitroglycerin (anti-platelet aggregation) + MPC (adhesion reduction) + tropoelastin (improved compliance) + RGD peptide (endothelialization promotion), the overall improvement of anti-thrombosis performance is achieved: the platelet adhesion amount is as low as 3 cells / mm2, which is significantly better than the single anti-thrombosis material loading group (Examples 1-5); the 30-day patency rate is 97%, which is the highest among all examples, and the calcification score is only 0.2, the anti-calcification effect is excellent; the endothelialization coverage rate is 89%, which shows that the synergistic effect of RGD peptide and tropoelastin effectively accelerates the vascular intima regeneration, further reducing the long-term thrombosis risk.
[0071] Comparative Example 1: No porous support layer is included Step 4) and Step 5) of Example 1 are directly applied to the expanded polytetrafluoroethylene embryo without a support layer. Specifically, the biodegradable material polylactic acid-glycolic acid copolymer PLGA (LA:GA=75:25, η=0.65 dL / g, 1.50 g) is dissolved in 10 mL of dichloromethane to form a 15 wt% solution. The expanded polytetrafluoroethylene tube blank without coating is vertically immersed 0.80 g at a uniform speed of 5 mm / s, the solvent is volatilized at room temperature, and the process is repeated twice to obtain a biodegradable layer with a thickness of 12 μm; the overall weight gain is 0.07 g.
[0072] Subsequently, the anti-thrombosis material is loaded to the embryo with the biodegradable layer in the manner of Step 5) of Example 1, wherein the loading density of heparin is 0.41 mg / cm2, and the grafting rate of phosphatidylcholine is 3.0%.
[0073] The test results of the artificial blood vessels are as follows: The performance test results of the artificial blood vessels prepared are as follows: From the above results, it can be seen that in the case of expanded polytetrafluoroethylene without a support layer, the burst strength is below the lower limit of 500 mmHg, and the compliance is too high, which does not match the natural artery, and in addition, thrombosis occurs in the rabbit carotid artery experiment.
Claims
1. A method for preparing an artificial blood vessel, the artificial blood vessel comprising a porous support layer, a biodegradable layer and an anti-thrombogenic layer, the method comprising: 1) dissolving N-isopropyl acrylamide monomers and vinyl pyrrolidone monomers in a first solvent, adding an initiator after oxygen removal treatment, performing a polymerization reaction at 60-80℃, and separating and purifying the reaction product polyvinyl pyrrolidone-poly-N-isopropyl acrylamide; 2) dissolving silver nitrate and the polyvinyl pyrrolidone-poly-N-isopropyl acrylamide prepared in step 1) in a second solvent to obtain a silver nitrate-doped polyvinyl pyrrolidone-poly-N-isopropyl acrylamide solution; 3) immersing expanded polytetrafluoroethylene in the silver nitrate-doped polyvinyl pyrrolidone-poly-N-isopropyl acrylamide solution prepared in step 2) so that the surface of the expanded polytetrafluoroethylene has a silver nitrate-doped polyvinyl pyrrolidone-poly-N-isopropyl acrylamide coating, and then removing the second solvent to obtain a porous support layer; 4) dissolving a biodegradable material in a third solvent, coating the dissolved biodegradable material on the surface of the porous support layer prepared in step 3) by immersion, spraying or brushing, and then removing the third solvent to obtain a porous support layer with a biodegradable layer; and 5) loading an anti-thrombogenic material to the porous support layer with a biodegradable layer obtained in step 4) to obtain the artificial blood vessel; wherein the first solvent is water or a mixture of ethanol and water; the second solvent is selected from N,N-dimethylformamide, dimethyl sulfoxide or a mixture thereof; and the third solvent is selected from dichloromethane, trichloromethane, N,N-dimethylformamide or a mixture of the above-mentioned solvents; wherein the initiator is ammonium persulfate, azobisisobutyronitrile or a mixture thereof; wherein the biodegradable material is one or more selected from polylactic acid, polycaprolactone, poly(lactic-co-glycolic acid), polyglycolide and polyurethane; and wherein the anti-thrombogenic material is one or more selected from heparin, nitroglycerin, phosphatidylcholine, tropoelastin, RGD peptide sequence, antithrombin III and tissue factor pathway inhibitor. In step 1), the ratio of the N-isopropyl acrylamide monomers to the vinyl pyrrolidone monomers is 1:9 to 9:1 (mol / mol), the ratio of the first solvent to the total mass of the monomers is 2:1 to 10:1, and the total mass of the initiator is 0.1wt%-2wt% of the total mass of the monomers. In step 2), the ratio of the silver nitrate to the polyvinyl pyrrolidone-poly-N-isopropyl acrylamide is 1:5-1:50 (wt / wt), and the solid content of the silver nitrate-doped polyvinyl pyrrolidone-poly-N-isopropyl acrylamide solution is 10wt%-15wt%. In step 3), the expanded polytetrafluoroethylene has a porosity of 50%-90% and an average pore size of micropores of 0.1-10μm. 2. The method of claim 1, wherein, 3. The method of claim 1, wherein, 4. The method of claim 1, wherein, 5. The method of claim 1, wherein, In step 4), the biodegradable material is a blend of polylactic acid and polycaprolactone, wherein the mass ratio of polylactic acid to polycaprolactone is 70:30 to 90:10; or the biodegradable material is a polylactic acid-glycolic acid copolymer, wherein the mass ratio of lactic acid to glycolic acid in the copolymer is 50:50 to 85:15; or the biodegradable material is a blend of polylactic acid and polyglycolide, wherein the mass ratio of polylactic acid to polyglycolide is 20:80-50:50; or the biodegradable material is a polyurethane, wherein the mass ratio of soft segment to hard segment in the polyurethane is 70:30 to 30:
70.
6. The method of claim 1, wherein, In step 5), the antithrombotic material is one of heparin, nitroglycerin ester, phosphatidylcholine, tropoelastin, and RGD peptide sequence, wherein the heparin is covalently immobilized on the surface of the porous support layer with a biodegradable layer obtained in step 4) by plasma grafting technology, and the surface density of the heparin is 0.1-1 mg / cm²; wherein the nitroglycerin ester is immobilized on the surface of the porous support layer with a biodegradable layer obtained in step 4) by chemical grafting or physical adsorption, and the content of the nitroglycerin ester on the surface is 0.5-2 wt%; wherein the phosphatidylcholine is grafted to the surface of the porous support layer with a biodegradable layer obtained in step 4) by ultraviolet grafting polymerization, and the grafting rate is 1-5%; wherein the tropoelastin is loaded on the surface of the porous support layer with a biodegradable layer obtained in step 4) by electrospinning or immersion, and the content of the tropoelastin on the surface is 1-10 wt%; wherein the RGD peptide sequence is immobilized on the surface of the porous support layer with a biodegradable layer obtained in step 4) by chemical grafting or physical adsorption, and the surface density of the RGD peptide is 1-10 nmol / cm².
7. The method of claim 1, wherein, The antithrombotic material is heparin and phosphatidylcholine, wherein the heparin is loaded on the surface of the porous support layer with a biodegradable layer obtained in step 4) by plasma grafting or immersion, and the phosphatidylcholine is then immobilized by chemical grafting, and the surface density of the heparin is 0.1-1 mg / cm²; and the grafting rate of the phosphatidylcholine is 1-5%.
8. The method of claim 1, wherein, The antithrombotic material is heparin, nitroglycerin ester, phosphatidylcholine, tropoelastin, and RGD peptide sequence, wherein the heparin is loaded on the surface of the porous support layer with a biodegradable layer obtained in step 4) by plasma grafting or immersion, and the nitroglycerin ester, phosphatidylcholine, tropoelastin, and RGD peptide are then sequentially immobilized by chemical grafting or physical adsorption, wherein the surface density of the heparin is 0.1-1 mg / cm²; the content of the nitroglycerin ester on the surface is 0.5-2 wt%; the grafting rate of the phosphatidylcholine is 1-5%; the content of the tropoelastin on the surface is 1-10 wt%; and the surface density of the RGD peptide is 1-10 nmol / cm².
9. The artificial blood vessel prepared by the method of claims 1-8.
10. The artificial blood vessel of claim 9, wherein, The porous support layer of the artificial blood vessel has a thickness of 2-5 μm, and the biodegradable layer of the artificial blood vessel has a thickness of 8-20 μm.
Citation Information
Patent Citations
Improved cardiovascular patch materials and method for producing same
WO1995001190A1
Improved PTFE vascular prosthesis and method of manufacture
WO1999047077A1
Immobilized biologically active entities having a high degree of biological activity
WO2009064372A3